Does ligand–receptor mediated competitive effect or penetrating effect of iRGD peptide when co-administration with iRGD-modified SSL?. (26th November 2015) - Zhang, Wei-Qiang; Yu, Ke-Fu; Zhong, Ting; Luo, Li-Min; Du, Ruo; Ren, Wei; Huang, Dan; Song, Ping; Li, Dan; Zhao, Yang; Wang, Chao; Zhang, Xuan
Abstract: Ligand-mediated targeting of anticancer therapeutic agents is a useful strategy for improving anti-tumor efficacy. It has been reported that co-administration of a tumor-penetrating peptide iRGD (CRGDK/RGPD/EC) enhances the efficacy of anticancer drugs. Here, we designed an experiment involving co-administration of iRGD-SSL-DOX with free iRGD to B16-F10 tumor bearing mice to examine the action of free iRGD. We also designed an experiment to investigate the location of iRGD-modified SSL when co-administered with free iRGD or free RGD to B16-F10 tumor bearing nude mice. Considering the sequence of iRGD, we selected the GPDC, RGD and CRGDK as targeting ligands to investigate the targeting effect of these peptides compared with iRGD on B16-F10 and MCF-7 cells, with or without enzymatic degradation. Finally, we selected free RGD, free CRGDK and free iRGD as ligand to investigate the inhibitory effect on RGD-, CRGDK- or iRGD-modified SSL on B16-F10 or MCF-7 cells. Our results indicated that iRGD targeting to tumor cells was ligand–receptor mediated involving RGD to αv-integrin receptor and CRGDK to NRP-1 receptor. Being competitive effect, the administration of free iRGD would not be able to further enhance the anti-tumor activity of iRGD-modified SSL. There is no need to co-administrate of free iRGD with the iRGD-modified nanoparticles for further therapeutic benefit.